Método de auditoría energética para motores eléctricos acorde a ISO 5000:22014 : Caso de estudio (2019)
The results of the implementation of an energy audit method for electric motors immersed in industrial factory production processes. It is based on the ISO 50002 standard and is applied in a case study at the Universidad del Cauca. It revolves around three fundamental axes; the first is the structuring of an energy audit method, which defines the procedure to be carried out in three-phase induction motors. The second is the implementation of the standard ISA-88.01 Models and Terminology, to perform a survey of information regarding the process of the audited case study, focusing on preparing a written, graphic and organized documentation of the physical assets involved in it. Finally, the IEEE standard 112-B is executed, for the calculation of the efficiency in three-phase induction motors. All of the above, with the aim of making an integral energy diagnosis in elements of final use of electrical energy, such as induction motors.